Haematological variables of Santa Ines and Ile de France suckling lambs: Influence of Haemonchus contortus infection - Lins, José Gabriel G. [UNESP] (2020)
Haemonchus contortus is the major gastrointestinal parasite of sheep raised in tropical and subtropical areas worldwide. This trial aimed to evaluate the influence of H. contortus infection on the bone marrow response of Santa Ines (SI) and Ile de France (IF) suckling lambs experimentally infected with H. contortus. Fourteen SI lambs and 12 IF lambs were randomized in four groups: infected SI (n=8), non-infected SI (n=6), infected IF (n=8) and non-infected IF (n=4). Lambs of infected groups were submitted to 27 infections, conducted every two days, from 14 to 68 days of age, and each lamb received a total of 5400 H. contortus infective larvae (L3). Ten blood samples were obtained during the experimental period to be used for erythrocyte and leukocyte counts, packed cell volume and total plasma protein estimation. Additionally, it was carried out a differential leukocyte count. Lambs from control groups did not shed eggs in faeces all over the experiment, while infected Santa Ines and Ile de France lambs presented means of 2963 EPG (Eggs Per Gram of faeces) and 8175 EPG in the last sampling (P<0.05), respectively. Infected Santa Ines lambs had an increase in eosinophil release, however differences (P<0.05) on circulation number in comparison with infected Ile de France lambs were identified only in the last sampling (54 days post first infection). The mild H. cortortus infection did not produce significant changes in the blood variables of the Ile de France and Santa Ines suckling lambs.